Utilization of Twitter as an Educational Tool to Improve Reading Literacy in Indonesian Language Students - Pratika, Sendy Dien; Jaja, Jaja; Rosmaya, Elin (Green Publisher Indonesia, 2024)
Digital power and lack of access to relevant literature. Twitter, as one of the most popular applications in the era of digital culture, can be used as an educational tool to increase the reading literacy of Indonesian language study program students. The integration of Twitter in the learning of Indonesian language study program students can facilitate access to information, increase creativity, develop reading literacy skills, expand social networks, and encourage student participation. The library research method is used to analyze secondary data from published research articles. The research question raised was,